Bovine viral diarrhea virus in China: A comparative genomic and phylogenetic analysis with complete genome sequences - Shah, Pir Tariq; Nawal Bahoussi, Amina; Ahmad, Aftab; Sikandar, Muhammad; Xing, Li (Frontiers in Veterinary Science, 2022)
Bovine viral diarrhea virus (BVDV), causing bovine viral diarrhea (BVD) in cattle, is one of the highly contagious and devastating diseases of cattle. Since 1980, BVDV has been identified all-over China in a variety of animal species including cattle, camels, yaks, sheep, water buffalo, goats, Sika deer and pigs. In this study, 31 BVDV complete genomes reported in China (from 2004-2020) with other 112 genomes reported around the world were comparatively analyzed. Phylogenetic analysis shows that BVDV genomes reported worldwide clustered in three major clades i.e., BVDV-1, BVDV-2, and BVDV-3. The BVDV-1 is genetically the most diverged genotype and phylogenetically classified into 7 sub-clades in our study based on full-length genomes. The China BVDV genomes fall into all three major clades, e.g BVDV-1, BVDV-2 and BVDV-3. China BVDV-1 clustered into five sub-clades, e.g 1, 2, 3, 6 and 7, where sub-clade 7 clustered as a separate sub-clade. Full-length genome recombination analysis reveals that the BVDV-1 reported in China appears to be mainly involved in recombination events. In addition, comparative analysis of E2 proteins between BVDV-1, BVDV-2, and BVDV-3 reveals that the amino acid variations could affect 12 potential linear B cell epitopes, demonstrating a dramatic antigen drift in the E2 protein. These results provide a thorough view of the information about the genetic and antigenic diversity of BVDVs circulating in China and therefore could benefit the development of suitable strategies for disease control.